Cuapetes Clark, 1919, a senior synonym of Kemponia Bruce, 2004 (Crustacea: Decapoda: Palaemonidae) - Okuno, Junji (Zootaxa, 2009)
Borradaile (1915) established Falciger Borradaile, 1915, as a subgenus of Periclimenes Costa, 1844, for nine species described by him as new to science: Periclimenes (Falciger) nilandensis Borradaile, 1915; P. (F.) affinis Borradaile, 1915; P. (F.) dubius Borradaile, 1915; P. (F.) compressus Borradaile, 1915; P. (F.) brocketti Borradaile, 1915; P. (F.) pottsi Borradaile, 1915; P. (F.) suvadivensis Borradaile, 1915; P. (F.) seychellensis Borradaile, 1915; and P. (F.) kolumadulensis Borradaile, 1915. Two years later, Borradaile (1917) increased the number of species in the subgenus up to 27, and designated Periclimenes petitthouarsi var. spinifera De Man, 1902, now considered to be Periclimenella spinifera (De Man, 1902), as the type species of the subgenus. Subsequently, Holthuis (1955) designated P. (F.) nilandensis as the type species because Periclimenes petitthouarsi var. spinifera was not included in the original description of Falciger by Borradaile (1915) (see ICZN 1999: Article 67.2). Earlier, Clark (1919) had proposed a replacement generic name Cuapetes Clark, 1919 for Borradaile’s Falciger, since the latter name is a junior homonym of Falciger Say, 1824 (Insecta: Coleoptera), Falciger Bucholz, 1869 (Arachnida: Arachnoidea), and Falciger Trouessart and Mégnin, 1883 (Arachnida: Arachnoidea) (see Holthuis 1993). Following current nomenclatorial rules, the type species of Cuapetes must thus be regarded to be P. (F.) nilandensis (see ICZN 1999: Article 67.8). Until now, shrimp taxonomists have always considered Cuapetes as a junior synonym of Periclimenes sensu lato (see Holthuis 1993; Chace and Bruce 1993), but a situation is herein corrected.